Frequency Regulation in Hybrid Power System using Red-Tailed Hawk Algorithm based Fractional Order Controllers - Pandey R.K.; Gupta D.K.; Jha A.V.; Appasani B.; Dei G.; Samal S. (My University, 2025)
This paper presents the application of newly developed Red-Tailed Hawk (RTH) algorithm based fractional order PID controller for LFC of hybrid power system. The study focuses on a two-area power system with thermal, hydro, wind and gas turbine power plant. The effectiveness of the proposed approach is demonstrated through comparisons with PSO and GWO based controllers, applied to the same interconnected system. Tuning of controllers parameters have been done using RTH optimization technique by minimizing Integral of Time-multiplied by Absolute Error performance index. Additionally, robustness of the proposed concept is demonstrated with varying step load demand across a wide range of conditions. Furthermore, we extend the proposed approach to a more realistic power system model that incorporates physical constraints, including the reheat turbine, GRC, GDB and boiler dynamics. The paper evaluates the effectiveness of the concept through simulation studies and case examples, aiming to gauge its impact on enhancing frequency stability across various operating conditions. © 2024 IEEE.